Study on QSPR Method for Theoretical Calculation of Boiling Point of Some Organic Compounds - Ashrafi, F.; Rostami, A.A.; Mahdavipour, N. (Asian Journal of Chemistry, 2010)
Quantitative structure-property relationship (QSPR) models based on molecular descriptors derived from molecular structures have been developed for the prediction of boiling point using a set of 25 organic compounds. The molecular descriptors used to represent molecular structure include topological indices and constitutional descriptors. Forward stepwise regression was used to construct the QSPR models. Multiple linear regressions is utilized to construct the linear prediction model. The prediction result agrees well with the experimental value of these properties.